Aspectos de qualidade, balneabilidade e trofia das águas de praias da margem direita do Baixo Rio Tapajós - LEMOS, Edivaldo Junior de Souza (Universidade Federal do Oeste do Pará, 2021)
Tapajos river is an important river of clear water from Amazon Hydrographic basin. Due to it presents high-water availability with transparent water bordered by white sand, the river has become attractive for several activities, such as, among others water supply, recreation and leisure. The environmental quality degradation, caused mainly by anthropic factors, causes immediate impact to the water courses. In this context, monitoring the water resources is in fundamental importance to the maintenance of the water quality and to the human well-being. In this manner, this study aims to evaluate the water quality conditions of the beaches on the right bank from lower Tapajos River, in terms of bathing, trophy and superficial water patterner, in the municipality of Santarem – Pará. For this purpose, the following beaches were sampled along the right bank of the Tapajos River: Mureta, Cajueiro, Ponta de Pedras, Pajuçara and Maracanã. Then, it was done field and laboratory analyses from the fundamental parameter sets that compose the bathing conditions of the beaches and the WQI (Water Quality Index) and the TSI (Trophic State Index). Four monitoring campaigns were carried out in two phases of the fluvial hydrograph: low water (December 2015 and January 2017) and high water (May 2016 and May 2018). The results showed that the bathing conditions as in proper compliance situation, except in Maracanã beach that presented an improper condition in the year of 2015 and 2018. For the indices assessed, the WQI and the TSI results show that the beaches investigated have good quality and low eutrophication potential. These results indicate that Tapajos River, in the assessed section, presents good environmental conditions, such as relatively conserved marginal forest areas, high water availability and capacity of purify substances even in low season.